Utility and ruin probability relationship through premium equivalence (2015)
Utility is a satisfaction received from consuming a commodity or service. Ruin probability is the probability that an insurer's surplus will fall below zero for a certain period of time. While many researches have focused on the pricing of insurance premium using the concept of utility functions some have focused on finding the probability that the company or insurer will be insolvent at any given point via the ruin probability. This paper focused mainly on the calculation of the insurance premium by setting a tolerance level for the ruin probability. After the premium was solved, the corresponding utility was determined.

It was assumed that the loss or claims amount follows an exponential distribution or geometric distribution. A closed form expression for the finite-time ruin probability was determined. This closed form expression were used to generate algorithm that calculated the corresponding ruin probability. Computer programs were constructed for these calculations using scilab.
Keywords: Utility theory; Probabilities -- Insurance